Kesulitan Menulis Aksara Jawa dalam Pembelajaran Luring dan Daring (Studi Kasus di Kelas VIII SMP Negeri 1 Kebakkramat) - Rissafitri Sariyanti; Sumarwati Sumarwati; Dewi Pangestu Said (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2024)
The problem in this research is motivated by the difficulty of writing Javanese characters in offline and online learning. This research aimed to determine the Javanese language learning process in Javanese characters material offline and online, to describe the difficulties of writing Javanese characters, and to describe the factors causing the problems in writing Javanese characters. This research method uses qualitative descriptive research with a case research approach. The results showed that offline and online learning went well, but difficulties in writing Javanese characters were still found. The challenges in writing Javanese characters that were found include not being able to write quickly in a short time, difficulty determining the exact and correct Javanese characters, difficulty determining the sandhangan and pair of Javanese characters, difficulty distinguishing the form of Javanese characters, and dependence with notebooks. The factors causing the problem of writing Javanese characters come from internal and external factors. Internal factors include less motivation, lack of exercise, no interest, no confidence, and less student response. External factors include differences in the concept of writing latin letters and Javanese script, teacher differences in class levels, less conducive classes, lack of parental control, limited learning time, and changes in offline and online learning systems.